Spinal metastas,is of hepatoma - Benedek, Pedro; Gómez Haedo, Carlos; Medoc, Juan; Gravina, Francisco; Purriel, Juan; Estable, Miguel; Touya, Eduardo (Cirugía del Uruguay, 1979)
The authors present a case of disseminated hepatocarcinoma (hepatoma) in a cirrhotic patient with a cauda equina compression syndrome due to a spinal extradural metastasis.